AL-QUR'AN INSIGHTS ABOUT MUSYAWARAH (A Study of Maudhu'iy Commentary on Deliberation) - Makbul, M; Bakar, Achmad Abu; Parhani, Aan; Ahmad, La Ode Ismail (Program Pascasarjana, UIN Alauddin Makassar, 2021)
Various kinds of problems occur and have not been able to be resolved in themselves, families, until the nation and state have carried out various ways in an effort to resolve these problems, one of the methods recommended and ordered in the Qur'an is deliberation, what is the nature of deliberation and how the existence, essence and urgency of deliberation will be described in this discussion. This paper attempts to explain these three aspects to give us an idea of the concept of deliberation in the perspective of maudhu'iy. This study will describe the definitions, objects, principles to the benefits of deliberation in the perspective of the Qur'an.